2013
DOI: 10.1371/journal.pone.0083274
|View full text |Cite|
|
Sign up to set email alerts
|

A Replicating Modified Vaccinia Tiantan Strain Expressing an Avian-Derived Influenza H5N1 Hemagglutinin Induce Broadly Neutralizing Antibodies and Cross-Clade Protective Immunity in Mice

Abstract: To combat the possibility of a zoonotic H5N1 pandemic in a timely fashion, it is necessary to develop a vaccine that would confer protection against homologous and heterologous human H5N1 influenza viruses. Using a replicating modified vaccinia virus Tian Tan strain (MVTT) as a vaccine vector, we constructed MVTTHA-QH and MVTTHA-AH, which expresses the H5 gene of a goose-derived Qinghai strain A/Bar-headed Goose/Qinghai/1/2005 or human-derived Anhui Strain A/Anhui/1/2005. The immunogenicity profiles of both va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Recombinant MVA vaccines expressing the HA genes from various A/H5N1 influenza viruses have been constructed and tested for protective efficacy against challenge viruses belonging to different antigenic clades in animal models [ 95 ]. It has been shown that a rMVA expressing HA from the clade 1 A/H5N1 virus A/Vietnam/1194/04 can offer protection from homologous challenge, in addition to protection from several antigenically distinct A/H5N1 viruses in mice and macaques [ 96 , 97 , 98 , 99 , 100 ]. In mice, the rMVA-H5 vaccine induced high levels of HA-specific CD4 and CD8 T-cells targeting epitopes that are conserved among different HA clades [ 98 ].…”
Section: Preparing For Future Pandemicsmentioning
confidence: 99%
“…Recombinant MVA vaccines expressing the HA genes from various A/H5N1 influenza viruses have been constructed and tested for protective efficacy against challenge viruses belonging to different antigenic clades in animal models [ 95 ]. It has been shown that a rMVA expressing HA from the clade 1 A/H5N1 virus A/Vietnam/1194/04 can offer protection from homologous challenge, in addition to protection from several antigenically distinct A/H5N1 viruses in mice and macaques [ 96 , 97 , 98 , 99 , 100 ]. In mice, the rMVA-H5 vaccine induced high levels of HA-specific CD4 and CD8 T-cells targeting epitopes that are conserved among different HA clades [ 98 ].…”
Section: Preparing For Future Pandemicsmentioning
confidence: 99%
“…H5N1 A/QH virus was used to infect A549 and 293 T cells. The virus is characterized to spread rapidly via migratory birds and is likely the major agents for several human infections throughout Europe and China in the past few years [20, 21]. Interestingly, virus propagation was higher in A549 cells than in 293 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that more than 50 million people globally have died from influenza [2]. The highly pathogenic avian influenza (HPAI) H5N1 has infected thousands of people and spread globally in transported poultry or via indirect contact [3, 4]. Currently, it is impossible to eliminate the virus during its infection [5].…”
Section: Introductionmentioning
confidence: 99%
“…Two examples are provided. Attenuated vaccinia Tiantan [65,66] used in China for smallpox eradication is being assessed as a replication-competent vector for both HIV-1 [67] and H5N1 [68] vaccines and in its replication-defective form for hepatitis C vaccine [69]. Similarly, replication-competent adenovirus serotype 4 (Ad4) has been tested in humans as a vector for H5N1 [70] HIV and anthrax.…”
Section: Circulation Of Several Recombinant Vectors In the Same Targementioning
confidence: 99%